Burkina Faso : Sixth Review Under the Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria and Augmentation of Access. (IMF Staff Country Reports; Country Report ;, 2006)
Performance under the Poverty Reduction and Growth Facility-supported program has been good. All quantitative performance criteria have been met. The economy has coped well with unfavorable external price developments. A substantial reform of the mechanism for determining cotton producer prices is under way. The proposed new producer price mechanism for cotton is an improvement over the previous system. The maintenance of the fuel pricing mechanism, which ensures full pass-through of changes in world oil prices, and steps to privatize the state-owned telecommunication company are major accomplishments.